Potential of Müller Glia for Retina Neuroprotection. (3rd March 2020) - Eastlake, Karen; Luis, Joshua; Limb, G Astrid
ABSTRACT: Müller glia constitute the main glial cells of the retina. They are spatially distributed along this tissue, facilitating their close membrane interactions with all retinal neurons. Müller glia are characterized by their active metabolic functions, which are neuroprotective in nature. Although they can become reactive under pathological conditions, leading to their production of inflammatory and neurotoxic factors, their main metabolic functions confer neuroprotection to the retina, resulting in the promotion of neural cell repair and survival. In addition to their protective metabolic features, Müller glia release several neurotrophic factors and antioxidants into the retinal microenvironment, which are taken up by retinal neurons for their survival. This review summarizes the Müller glial neuroprotective mechanisms and describes advances made on the clinical application of these factors for the treatment of retinal degenerative diseases. It also discusses prospects for the use of these cells as a vehicle to deliver neuroprotective factors into the retina.